MODERN TECHNOLOGIES IN EDUCATION - Hasanboyeva Barno Sherali qizi; Islamova Xolida Xamza qizi (TADQIQOTLAR.UZ, 2024)
Abstract: Without a doubt, technology has changed the way we live. It has changed many facets of life and altered what it means to live. With the aid of new generations, several difficult and important tasks may be completed with ease. Education has undergone a transformation thanks to technology. Projectors in classrooms and universities have the power to significantly increase student engagement and interaction. As this idea gains more traction and recognition, it will only grow. Based on our study, the majority of individuals use live chat solutions. The most frequent chore in technology is searching for a job.